Heterologous production and biochemical characterization of a new highly glucose tolerant GH1 β-glucosidase from Anoxybacillus thermarum. (December 2020) - Almeida, Paula Zaghetto de; Oliveira, Tássio Brito de; Lucas, Rosymar Coutinho de; Salgado, José Carlos Santos; Pérez, Malena Martínez; Gálan, Beatriz; García, José Luis; Polizeli, Maria de Lourdes Teixeira de Moraes
Graphical abstract: Highlights: A novel recombinant β-glucosidase from Anoxybacillus thermarum (BgAt) is described. BgAt is purified in one step using affinity chromatography. BgAt GH1 is very thermostable and it is glucose / xylose tolerant. BgAt has high Vmax and great potential to hydrolyze biomass. Abstract: The enzymatic lignocellulosic biomass conversion into value-added products requires the use of enzyme-rich cocktails, including β-glucosidases that hydrolyze cellobiose and cellooligosaccharides to glucose. During hydrolysis occurs accumulation of monomers causing inhibition of some enzymes; thus, glucose/xylose tolerant β-glucosidases could overcome this drawback. The search of new tolerant enzymes showing additional properties, such as high activity, wide-pH range, and thermal stability is very relevant to improve the bioprocess. We describe a novel β-glucosidase GH1 from the thermophilic Anoxybacillus thermarum (BgAt), which stood out by the robustness combination of great glucose/xylose tolerance, thermal stability, and high Vmax. The recombinant his-tagged-BgAt was overexpressed in Escherichia coli, was purified in one step, showed a high glucose/xylose tolerance, and activity stimulation (presence of 0.4 M glucose/1.0 M xylose). The optimal activity was at 65 °C - pH 7.0. BgAt presented an extraordinary temperature stability (48 h – 50 °C), and pH stability (5.5–8.0). The novel enzyme showed outstanding Vmax values compared to other β-glucosidases. Using p-nitrophenyl-β-d -glucopyranoside as substrate the values were Vmax (7614 U/mg), and KM (0.360 mM). These values suffer a displacement in Vmax to 14, 026 U/mg (glucose), 14, 886 U/mg (xylose), and KM 0.877 mM (glucose), and 1.410 mM (xylose).